Monitoring sulfide-oxidizing biofilm activity on cement surfaces using non-invasive self-referencing microsensors. (1st February 2016) - Cheng, Liqiu; House, Mitch W.; Weiss, W. Jason; Banks, M. Katherine
Abstract: Microbially influenced corrosion (MIC) in concrete results in significant cost for infrastructure maintenance. Prior studies have employed molecular techniques to identify microbial community species in corroded concrete, but failed to explore bacterial activity and functionality during deterioration. In this study, biofilms of different sulfur-oxidizing bacteria compositions were developed on the surface of cement paste samples to simulate the natural ecological succession of microbial communities during MIC processes. Noninvasive, self-referencing (SR) microsensors were used to quantify real time changes of oxygen, hydrogen ion and calcium ion flux for the biofilm to provide more information about bacterial behavior during deterioration. Results showed higher transport rates in oxygen consumption, and hydrogen ion at 4 weeks than 2 weeks, indicating increased bacterial activity over time. Samples with five species biofilm had the highest hydrogen ion and calcium ion transport rates, confirming attribution of acidophilic sulfur-oxidizing microorganisms (ASOM). Differences in transport rates between three species samples and two species samples confirmed the diversity between Thiomonas intermedia and Starkeya novella . The limitations of SR sensors in corrosion application could be improved in future studies when combined with molecular techniques to identify the roles of major bacterial species in the deterioration process. Highlights: Noninvasive, self-referencing microsensors were applied for microbial corrosion monitoring. Real time biofilm change of oxygen flux was measured to represent biofilm metabolism. Real time biofilm changes of H + and Ca 2+ flux was measured to represent microbial corrosion. Results showed higher hydrogen and calcium transport rate from acidophilic Thiobacillus species.